A co-design of clinical virtual care pathways to engage and support families requiring neonatal intensive care in response to the COVID-19 pandemic (COVES study). Issue 6 (December 2021) - Campbell-Yeo, Marsha; Dol, Justine; Richardson, Brianna; McCulloch, Holly; Hundert, Amos; Foye, Sarah; Dorling, Jon; Afifi, Jehier; Bishop, Tanya; Earle, Rebecca; Elliott Rose, Annette; Inglis, Darlene; et al.
Abstract: Background: In response to the COVID-19 pandemic, family presence restrictions in neonatal intensive care units (NICU) were enacted to limit disease transmission. This has resulted in communication challenges, negatively impacting family integrated care. Aim: To develop clinical care pathways to ensure optimal neonatal care to support families in response to parental presence restrictions imposed during the COVID-19 pandemic. Methods: An agile, co-design process utilizing expert consensus of a large interdisciplinary team and focus groups and semi-structured interviews with families and HCPs were used to co-design clinical virtual care pathways. Results: Three clinical virtual care pathways were co-designed: (1) building and maintaining relationships between family and healthcare providers; (2) awareness of resources; and (3) standardized COVID-19 messaging. Modifications were made to optimize uptake and utilization in the clinical areas. Conclusion: Clinical care virtual pathways were successfully co-designed to meet these needs to ensure more equitable family centered care.